Moonlight : the Halloween cat - Rylant, Cynthia; Sweet, Melissa (New York : HarperCollins, 2003)
Moonlight the cat loves everything about Halloween, from pumpkins to children to candy.
Keywords: Halloween -- Fiction; Cats -- Fiction